Promoting digital technologies in Nigeria’s social work practice (2021)
This research examined knowledge, usage, risks, and challenges associated with digital technologies (DTs) in social work practice (SWP) among social workers in Nigeria. The study adopted the survey research design and sampled 33 registered social workers from Oyo State Chapter of the Nigerian Association of Social Workers (NASoW) using a purposive sampling technique. Quantitative data were collected with the researcher's self-designed PDTSWPS tool which was validated by experts in the field for consistency with the research objectives and tested for internal consistency reliability coefficient by Cronbach Alpha which yielded the following results . 0.65,0.67 and 0.66 respectively. The study revealed that social workers deploy DTs using various DTs tools such as: computers, tablets, smartphones, the internet, emails and social media platforms for social casework interventions in Nigeria. The study also revealed that social workers have high knowledge of the risks associated with the usage of DTs for social work practice. These social workers faced DTs-related challenges which are ethical and operational. The study recommended that organisations should collaborate with professional associations such as NASoW to actively promote the usage of DTs for SWP among social workers in a digitally evolving nation like Nigeria. They should also train social workers on the usage of DTs tools and ensure that they comply with all the professional codes of ethics in their field of practice. The government should as well sign the social work profession’s bill to enable NASoW to professionalise social work practice in Nigeria and institutionalise the ethical usage of DTs for SWP among social workers in social casework interventions in Nigeria